The use of DNA database of biological evidence from sexual assaults in criminal investigations: A successful experience in Brasília, Brazil. (December 2015) - Ferreira, Samuel T.G.; Paula, Karla A.; Maia, Flávia A.; Svidizinski, Arthur E.; Amaral, Marinã R.; Diniz, Silmara A.; Siqueira, Maria E.; Moraes, Adriana V.
Abstract: The use of DNA databases has proved decisive in many types of criminal investigations. In sexual assaults and rapes, DNA databases and evidence may play a very important role in the investigations and in the identification of the perpetrators. In Brazil, until 2012 and 2013 there was no legislation regarding DNA databases of suspected perpetrators or convicted individuals. As there was no legislation concerning this subject and due to the need for solving crimes related to sexual assaults, the Instituto de Pesquisa de DNA Forense da Polícia Civil do Distrito Federal (Forensic DNA Research Institute of Federal District Civil Police) in Brasília, created in 1998, a DNA database of evidence collected in sexual-assaults cases to aid criminal investigations. The aim of this study is to demonstrate the successful experience of our Institute in aiding criminal investigations to solve sexual assaults cases and to identify perpetrators using this kind of DNA database. Forensic scientists using a DNA database of evidence from sexual assaults cases, working together with Federal District Civil Police authorities and investigators, found 78 serial rapists who attacked 223 women in Brasília, Brazil.